My penguin pal : o desenvolvimento da proficiência linguística através do jogo eletrônico : Club Penguin - Smolinski, Conie Helena (Universidade do Vale do Rio dos Sinos, 2012)
The present study examines the effects of the introduction of the electronic game Club Penguin (available in videogame and in virtual environment - www.clubpenguin.com) into the private English classes as a second language (L2) to seven-year-old twin students. The advance in technology has brought up its own culture – the cyberculture, which also fascinates kids and may be explored to enhance learning. We have used, for this research, a sociocultural theoretical base, grounded on the work of Vygotsky, and we have looked at a new approach of that, considering it to the context of electronic games. The data has been collected through audio and video recordings, and through the diary and documents produced in class, during the second semester of 2010. By means of qualitative analysis, we have noticed that the characteristics of playing and learning are amplified in the digital environment, as well as the possibilities of interactions among players. We have assessed that the participants of this research have had progress at the Zone of Proximal Development, stimulated by the practice of scaffolding among pairs or with the teacher. They have also acquired the L2 vocabulary, structures and culture; increased the time dedicated to the game (and, consequently, to L2 study); and expanded the use of L2 in class.
Keywords: Jogos eletrônicos; Cybercultura; Segunda língua (L2); Club Penguin; Zona de Desenvolvimento Proximal (ZDP); Andaimento; Eletronic games; Cyberculture; Second language (L2); Zone of Proximal Development (ZPD); Scaffolding; ACCNPQ::Lingüística, Letras e Artes::Lingüística